Root Responses are Indicators for Salinity and Drought Stress in Crops - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
Degradation of cultivable lands to saline and drought prone conditions and reduced availability of water for agriculture are the two most severeproblems for modern agriculture. Development of salinity stress and drought stress tolerant crop genotypes is going to be the most daunting task for the plant breeders in the coming decades. To add to the misery of plant breeders, few effective selection indices are available that can help them to accurately identify the tolerant genotype under field conditions……